Tracing The Digital Footprint of The Organisation Persatuan Islam: Transformation, Strategy, and Representation of Religious Values in the Cyberspace - Raafi Herdiansyah Putra; Moh Rodi; Andri Rosadi; Mochamad Sodik (PERADA, 2025)
Religious organisations in Indonesia have undergone a digital transformation process that has brought significant changes to various aspects of religious life, including those carried out by Persatuan Islam (Persis), as one of the Islamic organisations that has long existed in Indonesia. This research uses a descriptive qualitative method with data collection techniques in the form of documentation from Persis official website and social media. This article aims to explain the form of digital transformation, digital communication strategies, and reveal the representation of religious values displayed by Persis. The results of this study show that the digital transformation carried out by Persis is in the form of digitalisation of da'wah in online media and crowdfunding in the form of digital fund collection and payment. The digital communication strategy carried out by Persis targets media selection in the form of websites, social media Youtube, Instagram, and Facebook with a flexible communication style according to the media used. The target audience is urban communities and young people who have easier access to the internet. The values displayed in Persis da'wah target various aspects including education, Islamic law, faith, solidarity between people, and various other dimensions related to teaching and internalising Islamic teachings. Various digital transformations carried out by Persis are carried out as an effort to maintain the existence of a long-established organisation.